Knowledge Sharing and Intellectual Capital Development of Deposit Money Banks in Rivers State, Nigeria - Obichere, Stanley Chijioke; Christine A. Nwuche (American Journal of Economics and Business Management, 2021)
This study examined the relationship between knowledge sharing and intellectual capital development of deposit money banks in Rivers state, Nigeria. The cross-sectional survey was adopted and a total population of four hundred and eighty-nine (489) from twenty (20) deposit money banks in rivers state, Nigeria, was covered. A sample size of two hundred and twenty (220) were drawn from the population. The simple random sampling technique was utilized in the study. However, only 198 copies of questionnaires retrieved were completely filled and used for the study. The Spearman rank were used to analyze the bivariate hypothesis while the Partial correlation was used in determining the moderating influence of psychological contract fulfilment on the relationship between the variables. The result of the bivariate analysis revealed that organizational communication has a significant relationship with human capital and relational capital while the multivariate hypothesis reveals that Psychological contract fulfilment moderates the relationship between knowledge sharing and intellectual capital development. Based on the findings, it was concluded that enhancing psychological contract fulfilment will help attract and retain well talented workforce which will subsequently result in increased knowledge sharing and thus improve the intellectual capital development of deposit money banks in Rivers state, Nigeria. The study recommended among others that the management of deposit money banks should ensure regular training of their employees as such will increase their knowledge and thus improve the Intellectual capital of deposit money banks in rivers state, Nigeria